Network-wise cerebral blood flow redistribution after 20 Hz rTMS on left dorso-lateral prefrontal cortex. Issue 101 (April 2018) - Shang, Yuan-Qi; Xie, Jun; Peng, Wei; Zhang, Jian; Chang, Da; Wang, Ze
Abstract: The repetitive application of transcranial magnetic stimulation (rTMS) on left dorsolateral prefrontal cortex (DLPFC) has been consistently shown to be beneficial for treating various neuropsychiatric or neuropsychological disorders, but its neural mechanisms still remain unclear. The purpose of this study was to measure the effects of high-frequency left DLPFC rTMS using cerebral blood flow (CBF) collected from 40 young healthy subjects before and after applying 20 Hz left DLPFC rTMS or SHAM stimulations. Relative CBF (rCBF) changes before and after 20 Hz rTMS or SHAM were assessed with paired-t test. The results show that 20 Hz DLPFC rTMS induced CBF redistribution in the default mode network, including increased rCBF in left medial temporal cortex (MTC)/hippocampus, but reduced rCBF in precuneus and cerebellum. Meanwhile, SHAM stimulation didn't produce any rCBF changes. After controlling SHAM effects, only the rCBF increase in MTC/hippocampus remained. Those data suggest that the beneficial effects of high-frequency rTMS may be through a within-network rCBF redistribution.